BUDAYA MEMBACA SEBAGAI IMPLEMENTASI GERAKAN LITERASI SEKOLAH DI MI MA’ARIF GONDOSULI MUNTILAN - Lailatul Munawwaroh; Samsul Arifin (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
This study aims to describe the implementation of the School Literacy Movement (GLS) at MI Ma'arif Gondosuli Muntilan. This study used a descriptive research design with a qualitative approach. The results showed that there was an implementation of the school literacy movement at MI Ma'arif Gondosuli Muntilan. The implementation includes: (1) adding enrichment books, as for the types of books available from textbooks, references and reading or enrichment books; (2) carrying out the habituation stage of literacy activities, as for activities such as holding reading activities 10-15 minutes before; (3) display of posters, including posters on the environment, traffic safety and invitations to read; (4) reading and writing activities in thematic learning.